The effects of Centella asiatica (L.) Urban on neural differentiation of human mesenchymal stem cells in vitro - Norazzila Omar; Yogeswaran Lokanathan; Zainul Rashid Mohd Razi; Ruszymah Bt Haji Idrus (BMC, 2019)
Abstract Background Centella asiatica (L.) Urban, known as Indian Pennywort, is a tropical medicinal plant from Apiaceae family native to Southeast Asian countries. It has been widely used as a nerve tonic in Ayuverdic medicine since ancient times. However, whether it can substitute for neurotrophic factors to induce human mesenchymal stem cell (hMSCs) differentiation into the neural lineage remains unknown. This study aimed to investigate the effect of a raw extract of C. asiatica (L.) (RECA) on the neural differentiation of hMSCs in vitro. Methods The hMSCs derived from human Wharton's jelly umbilical cord (hWJMSCs; n = 6) were treated with RECA at different concentrations; 400, 800, 1200, 1600, 2000 and 2400 μg/ml. The cytotoxicity of RECA was evaluated via the MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) and cell proliferation assays. The hWJMSCs were then induced to neural lineage for 9 days either with RECA alone or RECA in combination with neurotrophic factors (NF). Cell morphological changes were observed under an inverted microscope, while the expression of the neural markers S100β, p75 NGFR, MBP, GFAP and MOG was analyzed by quantitative polymerase chain reaction and immunocytochemistry. The cell cycle profile of differentiated and undifferentiated hWJMSCs was investigated through cell cycle analysis. Results RECA exerted effects on both proliferation and neural differentiation of hWJMSCs in a dose-dependent manner. RECA reduced the proliferation of hWJMSCs and was cytotoxic to cells above 1600 μg/ml, with IC50 value, 1875 ± 55.67 μg/ml. In parallel with the reduction in cell viability, cell enlargement was also observed at the end of the induction. Cells treated with RECA alone had more obvious protein expression of the neural markers compared to the other groups. Meanwhile, gene expression of the aforementioned markers was detected at low levels across the experimental groups. The supplementation of hWJMSCs with RECA did not change the normal life cycle of the cells. Conclusions Although RECA reduced the proliferation of hWJMSCs, a low dose of RECA (400 μg/ml), alone or in combination of neurotrophic factors (NF + RECA 400 μg/ml), has the potential to differentiate hWJMSCs into Schwann cells and other neural lineage cells.